Thoracolumbar Fractures Due to Speed-Humps: A Case Series of Spine Fractures from an Atypical Cause of Injury - Rogério P. Amorim; Vinícius M. Henriques; Lucas L. Santos; Fernando A. Vasconcelos; Alexandre M. Schmidt; Francisco L. Torrão; Hebert S. Junqueira; Carlos A. S. Moreira; Vinícius G. Reis; Fernando Guedes (Brazilian Neurosurgery)
This retrospective case series investigates thoracolumbar fractures resulting from speed humps during bus travel in Rio de Janeiro. The study encompasses 19 patients who experienced such fractures between 2013 and 2021 without collision events. Factors examined included demographics, injury specifics, management strategies, and outcomes. The study aims to elucidate the prevalence, characteristics, and treatment of these injuries. Analyses were conducted using clinical evaluations, AOSpine classification, Visual Analog Scale (VAS) for pain, and TL AOSpine Injury Score (TL AOSIS). Surgical and non-surgical interventions were compared, highlighting the need for strict traffic regulations and preventive measures to mitigate such accidents. Results reveal a predominance of fractures in women, with a mean age of 61.26 years, and an emphasis on L1 vertebra involvement. Surgical intervention was required in over 50% of cases, demonstrating favorable outcomes. However, limitations due to the study's retrospective nature and the tertiary care setting were acknowledged. The study concludes by emphasizing the importance of preventive measures, such as stricter traffic regulations, mandatory seatbelt use in public transportation, and enhanced speed-hump safety measures to curtail these accidents and subsequent injuries.